RECURRENT BREAST CANCER IN A POSTMENOPAUSAL WOMAN (CLINICAL CASE) - Елгина, Светлана Ивановна; Гафарова, Алина Радиковна; Рудаева, Елена Владимировна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна (Mother and Baby in Kuzbass, 2025)
Breast cancer is the most common malignant disease in women in the Russian Federation. In 2018, there were 70682 new cases, accounting for 20.9% of all malignant diseases in women. The average age of patients was 61.5 years. Over the past 10 years, the average annual growth rate of breast cancer (standardized rate) has been 1.97%. In recent years, there has been an increase in the number of patients diagnosed with breast cancer in the early stages. The standardized mortality rate decreased from 2008 to 2018, from 17.05 to 14.02, respectively. The risk of dying from breast cancer in women was 1.6% in 2018. The proportion of women who have been registered for 5 years or more is 59.8%. In the structure of female mortality, breast cancer also ranks first, accounting for 16.2%.The presented article describes a clinical case of recurrent primary multiple breast cancer.
Keywords: breast cancer; incidence; and mortality